The effect of wheel size on mobility performance in wheelchair athletes - Mason, B.; van der Woude, L.; Lenton, J. P.; Goosey-Tolfrey, V. L. (International Journal of Sports Medicine, 2012)
The purpose of the current study was to investigate the effects of different wheel sizes, with fixed gear ratios, on maximal effort mobility performance in wheelchair athletes. 13 highly trained wheelchair basketball players, grouped by classification level, performed a battery of 3 field tests in an adjustable wheelchair with 3 different wheel sizes (0.59 m, 0.61 m and 0.65 m). Performance was assessed using the time taken to perform drills, with velocity and acceleration data also collected via a wheelchair velocometer. 20 m sprint time improved in the 0.65 m condition (5.58±0.43 s, P=0.029) compared with 0.59 m (5.72±0.40 s). Acceleration performance over the first 2 (P=0.299) and 3 (P=0.145) pushes was not statistically influenced by wheel size. However, the peak velocities reached were greater in the 0.65 m condition (4.77±0.46 m?s - 1, P=0.078, Effect Size [ES]=0.63) compared with 0.59 m (4.61±0.40 m?s - 1). Impact velocity, calculated as the change in velocity from the onset of a push to the following impact peak, to define coupling performance, was also significantly improved in 0.65 m wheels (0.14±0.14 m?s - 1, P=0.006) than 0.59 m wheels (0.05±0.10 m?s - 1). The time taken to complete the linear mobility (P=0.630) and the agility drill (P=0.505) were not affected by wheel size. Finally, no significant interactions existed between wheel size, classification and any performance measure. To conclude, larger 0.65 m wheels improved the maximal sprinting performance of highly trained wheelchair basketball players, without any negative effects on acceleration or manoeuvrability. Improvements in sprinting were attributed to a combination of the reduced drag forces experienced and improvements in coupling thought to be due to the lower angular velocities of the wheel/hand-rim when developing high wheelchair velocities in larger wheels.